2010
DOI: 10.2165/11319760-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Estrogen on Skeletal Muscle

Abstract: As women enter menopause, the concentration of estrogen and other female hormones declines. This hormonal decrease has been associated with a number of negative outcomes, including a greater incidence of injury as well as a delay in recovery from these injuries. Over the past two decades, our understanding of the protective effects of estrogen against various types of injury and disease states has grown immensely. In skeletal muscle, studies with animals have demonstrated that sex and estrogen may potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
209
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(234 citation statements)
references
References 152 publications
6
209
3
3
Order By: Relevance
“…The absolute volume of skeletal muscle differs between genders and estrogen is known to play essential roles in both muscle [47,48] and NAFLD [49]. However, a previous study also showed that the effects of SMI on fatty liver did not differ between preor post-menopausal women [46].…”
Section: Discussionmentioning
confidence: 93%
“…The absolute volume of skeletal muscle differs between genders and estrogen is known to play essential roles in both muscle [47,48] and NAFLD [49]. However, a previous study also showed that the effects of SMI on fatty liver did not differ between preor post-menopausal women [46].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, hypogonadal men who produce lower levels of endogenous testosterone have reduced muscle mass compared with their eugonadal counterparts (62). Exogenous administration of both testosterone (4) and estrogen (11) influences muscle phenotype in humans. Supraphysiologic doses of androgens have been core components of doping programs in elite power sports for decades.…”
mentioning
confidence: 99%
“…Testosterone has been shown to induce muscle hypertrophy and lead to increases in voluntary strength (50). Estrogen has been shown to stimulate muscle repair and regenerative processes (11), although the extent and direction of the muscle response does seem contingent on species and circumstance (23,28,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Along with these definitions, much of the accompanying health information addresses symptoms, risk for associated diseases, and treatment options. This information fits the overall medical paradigm that menopause is not simply Epidemiological evidence indeed shows that the period surrounding and following menopause is associated with an increased prevalence of disease and disease risk factors, particularly those relating to the metabolic syndrome including weight gain, body composition change, obesity, hyperlipidemia, hypertension, and insulin resistance, all of which increase risk for heart attack, stroke, and type 2 diabetes (Torrens et al 2009;Enns and Tiidus 2010). In the…”
mentioning
confidence: 56%